2007
DOI: 10.1158/0008-5472.can-06-3735
|View full text |Cite
|
Sign up to set email alerts
|

Betulinic Acid Inhibits Prostate Cancer Growth through Inhibition of Specificity Protein Transcription Factors

Abstract: Betulinic acid is a pentacyclic triterpene natural product initially identified as a melanoma-specific cytotoxic agent that exhibits low toxicity in animal models. Subsequent studies show that betulinic acid induces apoptosis and antiangiogenic responses in tumors derived from multiple tissues; however, the underlying mechanism of action is unknown. Using LNCaP prostate cancer cells as a model, we now show that betulinic acid decreases expression of vascular endothelial growth (VEGF) and the antiapoptotic prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
301
2
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 273 publications
(339 citation statements)
references
References 45 publications
32
301
2
4
Order By: Relevance
“…Betulinic acid (BA), a natural pentacyclic triterpene isolated from birch, exhibits a variety of biological activities, including anti-HIV, anti-HBV, anti-malarial [8][9][10] and potent anti-tumor properties in melanoma [11] , leukemia [12] , colon [13] , lung [14] , gliomas [15] , prostate carcinoma [16] , gastric adenocarcinoma [17] and multiple myeloma [18,19] . Various mechanisms have been reported for the extensive anticancer activity of BA, including directly triggering mitochondrial membrane permeabilization [20] , regulating Bcl-2 family proteins [21] , downregulating Hiwi expression [17] and suppressing the activation of the STAT3 pathway through the induction of the protein tyrosine phosphatase SHP-1 [19] .…”
Section: Introductionmentioning
confidence: 99%
“…Betulinic acid (BA), a natural pentacyclic triterpene isolated from birch, exhibits a variety of biological activities, including anti-HIV, anti-HBV, anti-malarial [8][9][10] and potent anti-tumor properties in melanoma [11] , leukemia [12] , colon [13] , lung [14] , gliomas [15] , prostate carcinoma [16] , gastric adenocarcinoma [17] and multiple myeloma [18,19] . Various mechanisms have been reported for the extensive anticancer activity of BA, including directly triggering mitochondrial membrane permeabilization [20] , regulating Bcl-2 family proteins [21] , downregulating Hiwi expression [17] and suppressing the activation of the STAT3 pathway through the induction of the protein tyrosine phosphatase SHP-1 [19] .…”
Section: Introductionmentioning
confidence: 99%
“…Betulinic acid, a pentacyclic terterpene, and its derivatives have been reported to possess a variety of biological properties (Yogeeswari and Sriram, 2005) (Soler et al, 1996), anti-bacterial, anti-cancer (Chintharlapalli et al, 2007;Fulda, 2008), and anti-infl ammatory activities (Recio et al, 1995). Although anti-HIV and anti-cancer activities of betulinic acid and its derivatives have been reported to be through the inhibition of HIV entry, HIV-proteases or reverse transcriptase (Fujioka et al, 1994;Yogeeswari and Sriram, 2005), and through increased degradation of the transcription factors specifi city protein 1 (Sp1), Sp3, and Sp4 (Chintharlapalli et al, 2007), respectively, the underlying mechanism of anti-infl ammatory property of betulinic acid has not been clearly demonstrated (Recio et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Although anti-HIV and anti-cancer activities of betulinic acid and its derivatives have been reported to be through the inhibition of HIV entry, HIV-proteases or reverse transcriptase (Fujioka et al, 1994;Yogeeswari and Sriram, 2005), and through increased degradation of the transcription factors specifi city protein 1 (Sp1), Sp3, and Sp4 (Chintharlapalli et al, 2007), respectively, the underlying mechanism of anti-infl ammatory property of betulinic acid has not been clearly demonstrated (Recio et al, 1995). The present results evidently demonstrate that betulinic acid signifi cantly suppresses the activity of transcription factor NF-kB, which has been reported to play a key role in the infl ammatory responses, through the inhibition of LPS-induced IKB degradation in the cytoplasm (Lee et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies with BetA showed selective cytotoxicity on a variety of tumor cell lines but not on normal cells [44] and induced apoptosis in neuroblastoma and glioblastoma cells through the activation of the mitochondrial pathway [45,46]. Interestingly, a report by Tan showed that BetA inhibited prostate cancer growth through inhibition of the transcription factors, specificity protein1 (Sp1), Sp3, and Sp4 which regulate VEGF and survivin expression [49]. Furthemore, BetA has been shown to inhibit constitutive activation of STAT3, Src kinase, JAK1 and JAK2 and induce the expression of the protein tyrosine phosphatase, SHP-1.…”
Section: Betulinic Acidmentioning
confidence: 99%